2017
DOI: 10.1519/jsc.0000000000002097
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Accuracy of Rating of Perceived Exertion-Based Load Prescription in Powerlifters

Abstract: This study assessed male (n = 9) and female (n = 3) powerlifters' (18-49 years) ability to select loads using the repetitions in reserve-based rating of perceived exertion (RPE) scale for a single set for squat, bench press, and deadlift. Subjects trained 3× per week. For 3 weeks on nonconsecutive days in the weekly order of hypertrophy (8 repetitions at 8 RPE), power (2 repetitions at 8 RPE), and strength (3 repetitions at 9 RPE), using subject-selected loads intended to match the target RPE. Bench press and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…The present results permit the acceptance of the second hypothesis of utilizing the RPE and in some way the neuromuscular signal to differentiate loading ranges based on 10% slot of 1RM percentages. The observed results are in line of previous studies with powerlifters (17,18) and recreationally resistance-trained individuals (9,32) Similar to the present study, Naclerio et al (32) reported that relative loads in BP could be clearly differentiated between light, moderate and heavy loads by perceived exertion. However, the study by Naclerio and colleagues was unable to further discriminate between 10% increments of 1RM as was observed in the present investigation for the first four ranges (30 <40% vs. 40 <50% vs. 50 <60% vs. 60 <70%); see Table 2.…”
Section: Mechanical Changes Estimated By Perceived Exertion and The Esupporting
confidence: 93%
“…The present results permit the acceptance of the second hypothesis of utilizing the RPE and in some way the neuromuscular signal to differentiate loading ranges based on 10% slot of 1RM percentages. The observed results are in line of previous studies with powerlifters (17,18) and recreationally resistance-trained individuals (9,32) Similar to the present study, Naclerio et al (32) reported that relative loads in BP could be clearly differentiated between light, moderate and heavy loads by perceived exertion. However, the study by Naclerio and colleagues was unable to further discriminate between 10% increments of 1RM as was observed in the present investigation for the first four ranges (30 <40% vs. 40 <50% vs. 50 <60% vs. 60 <70%); see Table 2.…”
Section: Mechanical Changes Estimated By Perceived Exertion and The Esupporting
confidence: 93%
“…Since there were only 3 failed “daily max” attempts among the 5 participants of the MAX group throughout the 10-week training intervention, the results of this pilot study suggest that PL athletes may be able to effectively self-adjust load by using the modified RPE scale and that doing so may be a beneficial approach to load management in PL training [ 10 , 19 ]. The PER group followed a percentage 1RM based training plan, though were instructed to not exceed RPE 9, while the MAX group self-adjusted load until an RPE of 9–9.5 was reached.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the first testing session all participants first underwent 4 weeks of familiarization with the resistance training version of the RPE scale based upon ‘repetitions in reserve’ [ 10 , 11 ]. The athletes were required to implement the modified RPE scale in their current training.…”
Section: Methodsmentioning
confidence: 99%
“…As such, the effects of experience level on the SEMs reported may be confounded as a result of differing ability to predict repetitions to MF when training using heavier or lighter loads. Greater predictive ability may therefore occur with heavier loads ( Zourdos et al, 2016 ; Helms et al, 2017 ). This may be reflective of the conflation between effort and discomfort described above as greater perceived discomfort occurs with lower load RT ( Fisher, Ironside & Steele, 2016 ; Fisher, Farrow & Steele, 2017 ).…”
Section: Discussionmentioning
confidence: 99%